Evaluation of anti-liver cancer activity and anticancer mechanism of one novel small molecule compound (THY-10A62) targeting FAK pathway - Huang, Wanqiu; Zou, Rong; Xu, Jie; Deng, Yuliang; Zhang, Dongping; Hu, Yiguo; Zhang, Qian; Huang, Jian; Zhang, Zhaoqi (Frontiers in Oncology, 2025)
IntroductionFocal adhesion kinase (FAK) is a promising therapeutic target, and its aberrant overexpression has been implicated in the growth and metastasis of multiple cancers, including hepatocellular carcinoma (HCC). This study preliminarily evaluated the antitumor activity and mechanisms of THY-10A62, a novel FAK inhibitor, in vivo.MethodsThe maximum tolerated dose (MTD) and median lethal dose (LD50) of THY-10A62 were determined in ICR mice using dose-escalation survival and tolerability assessments. Antitumor efficacy was tested in an HCC-LM3 cell line-derived xenograft (CDX) model and in patient-derived xenograft (PDX) models of liver cancer. FAK pathway modulation was examined using a protein phosphorylation chip coupled with network pharmacology analyses. FAK phosphorylation levels were measured in PDX tumors following treatment. Efficacy was benchmarked against PF-562271.ResultsThe MTD of THY-10A62 in mice was < 45 mg/kg, and the LD₅₀ in female mice was 49 mg/kg. At 15 mg/kg, THY-10A62 significantly inhibited liver tumor growth (TGI > 40%), with greater suppression than PF-562271 at the tested conditions. In PDX tumors, THY-10A62 markedly down-regulated FAK phosphorylation. Phospho-proteomic profiling indicated altered phosphorylation of downstream effectors, including BRAF and RASGRF1, consistent with inhibition of FAK-mediated signaling.DiscussionTHY-10A62 demonstrates in vivo antitumor activity against HCC with an acceptable tolerability window, supporting FAK as a viable target. The observed reductions in FAK phosphorylation and changes in BRAF and RASGRF1 phosphorylation suggest pathway-level modulation underlying efficacy. These findings provide preliminary evidence that THY-10A62 is a potential FAK inhibitor for liver cancer therapy and warrant further studies to refine dosing, characterize pharmacokinetics/toxicity, and validate efficacy across additional HCC models.